Design of Compact Dual Band Circular Polarized Micro-strip Antenna for High Efficiency WLAN 802.11ax-2019 - Syed Muhammad Ali (International Journal of Informatics and Communication Technology (IJ-ICT), 2018)
Design of antennas for the latest upcoming standards of WLANs is considered as a key challenge in the science of Mobile Communication Engineering. Micro strip antennas are supposed to have some quality features in mobile and wireless network systems. Their weight and size are reduced and they are capable of having low power capacity. All these interesting features enabled these type of antennas suitable for the communication of IEEE 802.11ax-2019 high speed WLANs. Shape of these antennas can be designed in an efficient manner to achieve required gain and bandwidth. In this paper the concept of circular polarization has been introduced along with compact design of antennas in order to achieve return loss and axial ratio of less than -10 dB and 3dB respectively. Antenna has been designed and simulated on CST MW studio software and usage of dual bands 2.4 and 5.2GHz having circular polarization is properly elucidated for 802.11ax-2019.